Implementasi Platform Visualisasi dan Analisis Trafik Jaringan menggunakan Arkime pada Jaringan Small-Office/Home-Office - Zaky Abdussalam; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Network Traffic Analysis is a process of gaining knowledge and conclusions related to information from observable data flow characteristics. These characteristics include the identity, location of the source and destination of the stream, the existence of the stream, the number, frequency, and duration of that stream of information. Continuous network monitoring and analysis helps in keeping the network at its performance with little downtime. One method that can be used to analyze network traffic is to utilize the Arkime platform. In this final project, Arkime will be applied to monitor network traffic by collecting traffic data and providing visualization of the data which will then be analyzed from the traffic data. The main components that make up this system are a managed switch and capture-node in which the Arkime platform configuration and elastic stack components are Elasticsearch, and Metricbeat. Arkime itself consists of two elements, arkime-capture as a package catcher and arkime-viewer for data analysis and visualization. In the data retrieval process, the data used is direct data from network traffic in the researcher's environment that is captured using the arkime-capture component. The built system will also be tested for resource usage performance at the time of data collection and using specific network loads.